Immunological Impact of Laser and Activated Carbon Nanoparticles on the Vaccination Efficiency with DTP Vaccine - Kaiser N. Madlum (Journal of Global Pharma Technology, 2018)
Objective(s): This work aimed to investigate the possibility of using laser vaccine adjuvant (LVA) to enhance deeply injected intramuscular vaccination. The second aim was to detect the effect of super activated carbon nanoparticles (SACNP) on the immune response.  Materials and Methods: (DTP) vaccine was used in this study to vaccinate male rats intramuscularly (i.m.), after irradiation with either red (λ=635 nm) or green (λ=532 nm) laser lights. Blood samples were collected 14 days later.  Results: LVA caused dynamic alteration of rat immune response. It caused a significant elevation in the pro-inflammatory cytokines (IL-1β & IL-6) and anti-inflammatory cytokine (IL-4) levels. SACNP showed an attractive effect on immune response especially in the presence of laser light. Conclusion: This paper demonstrates the applicability of LVA for intramuscular vaccination. Red laser and SACNP, which is a new form of nanoparticles, show an attractive effect on immune response.Keywords: DTP, Laser adjuvant, Vaccination, Cytokines, Immune response, Bio stimulation.